Physicochemical properties and antioxidant activity of oil extracted from Assam tea seeds (Camellia sinensis var. assamica) by supercritical CO2 extraction - Rattana Muangrat (2020)
© 2020 Wiley Periodicals, Inc. Response surface methodology (RSM), based on a central composite design, was used to simultaneously predict the optimal condition for oil extraction of Assam tea seeds via supercritical CO2 extraction method. The established regression mathematical model oil extraction was good enough for the prediction of experimental results (e.g., crude oil yield). The optimized extraction condition (50°C under 220 bar for 4 hr) providing the best quality of oil has high percentage of crude oil yield and oil recovery, low values of acid, free fatty acids, peroxide, and thiobarbituric acid reactive substances (TBARS), high values of iodine and saponification, and high phenolic content and low values of DPPH (IC50) and ABTS (IC50). Flavonoid, tannin, and saponin were detected in the extracted oil samples. In addition, major fatty acids in the extracted oil were oleic, linoleic, and palmitic acids. Practical applications: Supercritical CO2 extraction can potentially be used for the extraction of oil from Assam tea seeds (Camellia sinensis var. assamica), providing a high oil yield. Assam tea seed oil obtained by supercritical CO2 extraction had a high antioxidant activity. The main fatty acids were oleic acid, linoleic acid, and palmitic acid. The obtained oil contained flavonoids, tannins, and saponins and is, therefore, a potential source of active and functional compounds used in the food industry, the production of food supplements and the pharmaceutic and cosmetic industries.